Optical and photoluminescent properties of nanostructured hybrid films based on functional fullerenes and metal nanoparticles - Dmitruk, N.; Borkovskaya, O.; Naumenko, D.; Berezovska, N.; Dmitruk, I.; Meza-Laguna, V.; Alvarez-Zauco, E.; Basiuk, E. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2009)
The chemically cross-linked C₆₀ thin films, capable of binding Ag or Au nanoparticles, were prepared by the gas-phase treatment with diamine for one set of samples and dithiol for another one and decoration with Ag or Au nanoparticles, respectively. The optical and photoluminescent properties of the obtained nanostructured hybrid films in comparison with the undecorated films were studied. The low temperature photoluminescence (PL) spectra demonstrate significant changes of the band intensity and appearance of fine structure for bands connected with radiative transitions of self-trapped and localized excitons. The decoration of pristine and treated C₆₀ films with Ag nanoparticles leads to a decrease of PL intensity and to slight bandgap reduction. These phenomena can be explained by the increase of the surface recombination velocity at the fullerene-nanoparticle interface. At the same time, the nanoparticles insignificantly decrease the transmittance of light into the fullerene and Si layers, and have almost no influence on photoelectric properties of metal/fullerene/Si barrier structures.